Efektivitas Seleksi Perangkat Desa di Desa Sidomulyo Kecamatan Pule Kabupaten Trenggalek - Sunarso, Sunarso; Mirlana, Dendy Eta; Bilyastuti, Mai Puspadyna; Yulianto, Erwin (Universitas Indo Global Mandiri, 2025)
Selection is a step to choose people with predetermined qualifications in order to fill positions in an organization. This study aims to describe the effectiveness of village apparatus selection in Sidomulyo Village, Pule District, Trenggalek Regency. The type of research is qualitative descriptive research with a case study approach. Data collection techniques using observation, in-depth interviews and documentation studies. Respondents in this study were village heads, committee chairs, Bhabinkamtibmas, and community leaders. The data was successfully collected, processed and analyzed with the help of descriptive qualitative analysis techniques. The results of the study indicate that the selection of village apparatus is generally effective, seen based on 1) transparency of the recruitment process; 2) clarity of laws and regulations; 3) participant competence; 4) quality of the implementing committee; 5) supervision; 6) community involvement. The results of the selection passed competent participants according to the needs of the village government. The village security situation during 2020 to 2024 was safe and there were no disturbances, where during that period 4 village apparatus selection processes were carried out. The implication of this study is that if you want to increase the effectiveness of village apparatus selection, then village leaders, village elite figures and the entire community must commit to not committing fraud and nepotism.